1999
DOI: 10.1016/s0006-3495(99)76991-2
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Bioactive Peptides with an Immobilized Phosphatidylcholine Monolayer

Abstract: The interaction of three bioactive peptides, bombesin, beta-endorphin, and glucagon with a phosphatidylcholine monolayer that was immobilized to porous silica particles and packed into a stainless steel column cartridge, has been studied using dynamic elution techniques. This immobilized lipid monolayer provides a biophysical model system with which to study the binding of peptides to a lipid membrane. In particular, the influence of temperature and methanol concentration on the affinity of each peptide for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 57 publications
(70 reference statements)
2
28
0
Order By: Relevance
“…Linear van't Hoff plots were obtained with correlation coefficients r higher than 0.98 for all fits. It was previously demonstrated that for some solute molecule, their binding with a phosphatidylcholine monolayer can lead to a phase transition of the IAM surface around 25 • C [44]. In this work, the observed linear relationships excluded a phase transition of the immobilized phosphatidylcholine in the stationary phase over the range of experimental temperatures as it was observed for bile salt-membrane interactions [45].…”
Section: Thermodynamic Parameterssupporting
confidence: 63%
“…Linear van't Hoff plots were obtained with correlation coefficients r higher than 0.98 for all fits. It was previously demonstrated that for some solute molecule, their binding with a phosphatidylcholine monolayer can lead to a phase transition of the IAM surface around 25 • C [44]. In this work, the observed linear relationships excluded a phase transition of the immobilized phosphatidylcholine in the stationary phase over the range of experimental temperatures as it was observed for bile salt-membrane interactions [45].…”
Section: Thermodynamic Parameterssupporting
confidence: 63%
“…PHM, mGFP, and DsRed each adopt a stable, folded structure and have been crystallized (www.rcsb.org/pdb: 1RRX; 1ZGO; 1OPM; Zacharias et al, 2002). In contrast, NPY and ACTH, which are unstructured (Mozsolits et al, 1999;Thomas et al, 2005), showed little segregation; neither pro-NPY nor POMC has been crystallized (www.rcsb.org/pdb). The simplest hypothesis consistent with our data is an old one, namely that individual proteins dictate the extent of their segregation in part through their ability to self-associate (Figure 10).…”
Section: Self-aggregation: a Default Mechanism For Cargo Protein Sortingmentioning
confidence: 99%
“…To understand peptide-membrane interactions in detail, the role of numerous physicochemical parameters including peptide charge, hydrophobicity, amphipathicity and the degree of secondary structure and the angle subtended by the polar face, in the physicochemical interaction between peptides and the membrane have been analysed. A wide variety of biophysical techniques such as circular dichroism, nuclear magnetic resonance, fluorescence spectroscopy, Fourier transform infrared spectroscopy, attenuated total reflection Fourier transform infrared spectroscopy, immobilized artificial membrane chromatography combined with model membrane systems have been used to study biomolecular-membrane interactions [12][13][14][15]. These techniques have provided important information on specific structure-function relationships associated with peptide-membrane interactions.…”
Section: Marie-isabel (Mibel) Aguilarmentioning
confidence: 99%